Internalization of Living Qur'an Values for Millennial Generation in the Traditions of Birth, Marriage and Death in the Minangkabau Tribe - Muhammad Hanif Hanif; Suci Ramadhanti Febriani; Kaddour Guettaoi Bedra (Jurnal test, 2023)
This study aims to explore the values ​​of the Living Qur'an in the Millennial Generation based on Minangkabau ethnic background. This study used a case study design with 33 informants consisting of several universities with Minangkabau ethnic backgrounds even though the agencies they are sheltered from are from outside West Sumatra. Data collection techniques included limited observation, documentation of traditional activities in the surrounding environment and distribution of questionnaires with 20 questions via Google form, while data analysis used the Milles and Hubberman techniques. This research shows that the values ​​of the Living Qur'an in the Millennial Generation are applied to traditions developed in certain areas, such as traditions of birth, marriage and death. Basically, this research identifies that the internalization of the values ​​of the living Qur'an is still used even in the millennial generation environment. The research findings corroborate the values ​​of the Living Qur'an strengthen the activities of the millennial generation which are based on the sources of Al-Qur'an law. This research is still limited to samples and objects of study in the traditions of birth, marriage and death. On that basis, the researcher recommends identifying a variety of themes and a wider sample.